Interação da miltefosina com os componentes lipídicos e proteicos das membranas de eritrócito e Leishmania estudada por ressonância paramagnética eletrônica - Moreira, Rodrigo Alves (2014)
Cutaneous leishmaniasis is a neglected tropical disease that infects millions of people worldwide, representing a serious public health problem. The miltefosine (MT) is an alkylphospholipid that has been approved for the treatment of breast cancer metastasis and visceral leishmaniasis, although the mechanism of action at the molecular level is poorly understood. Electron paramagnetic resonance (EPR) spectroscopy of the lipid spin lebel analog of stearic acid (5-DSA) and the maleimide derivative spin label (6-MSL) covalently bound to membrane proteins showed that the MT causes a large increase in the molecular dynamics of erythrocyte membranes (ghosts) and detergent resistant membranes (DRMs) prepared from erythrocyte membranes. In the vesicles of lipid raft constituents, it was shown that 20 mol% sphingomyelin could be replaced by 20 mol% MT with no change in the molecular dynamics. Furthermore, the effect of MT on DRMs was more pronounced than in erythrocyte ghosts, supporting the hypothesis that MT is a lipid raft modulator. At the reported MT-plasma concentrations found during the treatment of leishmaniasis (31-52μg/mL), our measurements in blood plasma indicated a hemolytic level of 2-5% and also showed that the MT concentration that changes the erythrocyte membrane fluidity to an extent that is detectable by EPR spectroscopy causes about 46% hemolysis. Subsequently, EPR studies performed with the same spin labels in the membrane of Leishmania (L.) amazonensis (promastigote) showed changes similar to those found in erythrocyte membranes. Cytotoxic effects on the parasites were also evaluated to investigate the relationships between the cytotoxic potential of MT and its ability to alter membrane fluidity. The EPR data showed that the minimum concentration of MT required to cause a change in the parasite membrane occurred near the values of MT concentration which inhibits 50 % of cell growth (IC50); thus, there is a correlation between the cytotoxicity and changes in the membrane. Although these III membrane alterations can be detected using a spin-labeled lipid, our experimental results indicated that MT interacts predominantly with the protein component of the membrane. Cell lysis was also detected by analyzing the supernatants of centrifuged samples for the presence of spin-labeled membrane fragments and cytoplasmic proteins. Using a method for the rapid incorporation of MT into the membrane, these effects were measured immediately after treatment under the same range of MT concentrations that cause cell growth inhibition. Cytotoxicity, estimated via microscopic counting of living and dead cells, indicated ∼ 70% cell death at the concentration of MT at which EPR spectroscopy detected a significant change in membrane dynamics. After this initial impact on the number of viable parasites, the processes of cell death and growth continued during the first 4 h of incubation. The EPR spectra of spin-labeled membrane-bound proteins were consistent with more expanded and solvent-exposed protein conformations, suggesting a detergent-like action. Thus, MT may form micelle-like structures around polypeptide chains, and proteins with a higher hydrophobicity may induce the penetration of hydrophilic groups of MT into the membrane, causing its rupture.